Cognitive Flexibility Matters: The Role of Multilevel Positive Affect and Cognitive Flexibility in Shaping Victims' Cooperative and Uncooperative Behavioral Responses to Trust Violations. Issue 2 (April 2020) - Williams, Michele; Belkin, Liuba Y.; Chen, Chao C.
Despite a significant growth in the scholarly literature in the area of trust violations and repair in the last decade, extant work has largely ignored the complex and socially competent responses of the victims of these violations. Our framework integrates insights from affective events theory, the broaden-and-build theory of positive emotions, and theories of cognitive processing to suggest that cognitive flexibility is central to understanding how individuals respond to trust violations. Rather than viewing victims solely as gatekeepers to trust repair, we examine how victims' cognitive processes are influenced by the affective context of those violations, which can, in turn, produce a spectrum of nuanced behavioral responses. We refer to this spectrum as the "swollen middle, " the range of behavior that resides between the extremes of impulsive revenge and forgiveness-based, communal cooperation. By integrating psychological theories of emotion and cognitive processing, we seek to highlight the central role of cognitive flexibility in the range of cooperative responses to trust violations. More broadly, we seek to contribute to the emergence of a new paradigm for studying interpersonal trust at work—a paradigm that explores trust-violating events as situated affect-laden experiences that interact with relevant organizational and interpersonal factors to influence employee behavior and trust dynamics in organizations.